2016
DOI: 10.1073/pnas.1513918113
|View full text |Cite
|
Sign up to set email alerts
|

Remarkably low affinity of CD4/peptide-major histocompatibility complex class II protein interactions

Abstract: The αβ T-cell coreceptor CD4 enhances immune responses more than 1 million-fold in some assays, and yet the affinity of CD4 for its ligand, peptide-major histocompatibility class II (pMHC II) on antigen-presenting cells, is so weak that it was previously unquantifiable. Here, we report that a soluble form of CD4 failed to bind detectably to pMHC II in surface plasmon resonance-based assays, establishing a new upper limit for the solution affinity at 2.5 mM. However, when presented multivalently on magnetic bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
65
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 46 publications
12
65
2
Order By: Relevance
“…2 OR, z score statistic, and P value computed under the null hypothesis. Table 6-Characterizing associations of four selected amino acids in DRB1 with IA-2A-positive and 1A-2A-negative patients and their differences consistent with or against this hypothesis (33,(36)(37)(38)(39)(40)(41)(42)(43). One matter complicating all analyses is the considerable in vitro instability of the human CD4 molecule, necessitating in many cases the use of mutant forms that form stable complexes with HLA-DR molecules to obtain crystallization of CD4-HLA-DR complexes (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…2 OR, z score statistic, and P value computed under the null hypothesis. Table 6-Characterizing associations of four selected amino acids in DRB1 with IA-2A-positive and 1A-2A-negative patients and their differences consistent with or against this hypothesis (33,(36)(37)(38)(39)(40)(41)(42)(43). One matter complicating all analyses is the considerable in vitro instability of the human CD4 molecule, necessitating in many cases the use of mutant forms that form stable complexes with HLA-DR molecules to obtain crystallization of CD4-HLA-DR complexes (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CD8 can be effectively thought of as a bivalent molecule able to bind both pMHC and TCR to increase their association rate. It should be noted that the CD4/MHC‐II affinity is substantially lower than the CD8/MHC‐I affinity, and therefore, modulation of TCR/pMHC binding may be less important for CD4 (see below).…”
Section: Mechanisms Of T‐cell Sensitivity To Antigenmentioning
confidence: 99%
“…How the effective height of surface proteins affects protein distribution in cell-cell contacts will be discussed in the next section. However, protein exclusion from cell-cell contacts is also influenced by crowding effects, and it has been observed that proteins smaller than the gap size can also be excluded ( 16 , 18 , 23 , 65 , 66 ). This can be due to interactions with stationary adhesion molecules in the contact but also with mobile proteins on the contacting surface.…”
Section: Hydrodynamic Trappingmentioning
confidence: 99%